PERAN ENTERPRISE RESOURCE PLANNING (ERP) DALAM OPTIMALISASI RANTAI PASOK DI PABRIK PENGOLAHAN BAWANG MERAH: STUDI KASUS GUDANG BAWANG JONPITER SILAEN DI MEDAN - Dionisius Sihombing; Aurel Ramadhanti Surya; Waidan Nur Siregar; Hawila Sabta Pangaribuan; Ahmad Hidayat Pandia; Dhea Gysela Br Marpaung (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2026)
Shallot trading businesses face persistent challenges in supply chain coordination, particularly regarding unstable agricultural yields, pest infestations, and volatile commodity prices, which demand a more structured information management system. This study aims to examine how the Enterprise Resource Planning (ERP) framework can strengthen supply chain operations at Gudang Bawang Jonpiter Silaen in Medan City. A qualitative case study design was adopted, with in-depth interviews conducted with the business owner as the primary data source, supplemented by academic literature. Findings reveal that the business operates through interconnected stages sourcing shallots from farmers, warehouse storage, product grading, and distribution to market traders where existing documentation practices already mirror the core logic of ERP. The study concludes that transitioning toward a fully integrated ERP-based platform holds significant potential for improving operational productivity, reducing data inconsistencies, and sustaining a well-coordinated distribution network. It is recommended that the business gradually adopt a digital recording system that integrates procurement, inventory control, and sales transactions into a unified platform.